The Transparency Principle In Regional Development Banks To Implement Good Corporate Governance: A Case Study On Pt Bank Pembangunan Daerah Jawa Timur Tbk - Yuwana, Citranella Ramadhani; Dewi, Yetty Komalasari (Jurnal Hukum & Pembangunan, 2020)
This paper discusses the obligation of Regional Development Bank (RDB) as a Regionally-Owned Enterprises (ROE) to implement Good Corporate Governance (GCG). In particular, this paper analyzes the forms of transparency principle in RDB, specifically in PT Bank Pembangunan Daerah Jawa Timur Tbk (Bank Jatim) according to existing regulations. By using legal normative method, this paper concludes that the forms of transparency principle on RDB is divided into three parts, namely preparing reports, publishing them, and ensuring that they are publicly accessible. There are at least 8 (eight) forms of transparency principle implementation, namely monthly publication report, quarterly publication report, annual publication report, prime lending rate publication report, material information and facts publication report, information on banks product, information on the use of customers data, and GCG report.